Analisis Isi Pesan Dakwah Dalam Akun Instagram @twitt.sunnah - Dimas Subagja, Farhan; Chairiawaty; Parihat Kamil (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. Researchers chose the social media Instagram, which is easy to use for various groups. Instagram can be used as a business medium, sharing photos, videos, post history. In terms of convenience, Instagram has the privacy of viewing profiles, separate photos, reels. Researchers are interested in conducting a more in-depth study of the background, this Instagram account is worthy of research, judging from the proportion of responses from its followers, 98% positive and 2% not. Judging from the content, the posts are in the form of motivation, in terms of Islamic values, namely morals, aqidah and sharia. The aim of this research is to find out the messages contained in the Instagram account @twitt.sunnah, namely faith, shari'ah and morals. The researcher used a qualitative descriptive analysis method with Roland Barthes' semiotic theory, then the results of the analysis were linked to the arguments of the Al-Quran and Hadith. This research method produces descriptive data findings in the form of words, not numbers. Overall, the results of the analysis can be concluded that the da'wah messages found on the Instagram account @twitt.sunnah can be classified, namely: 5 aqidah messages, 9 moral messages, 8 shari'ah messages.. Abstract. Peneliti memilih media sosial Instagram yaitu mudah digunakan berbagai kalangan. Instagram bisa dijadikan media bisnis, membagikan foto, video, riwayat postingan. Instagram dari segi kenyamanan mempunyai privasi melihat profil, memisahkan foto, reels. Peneliti tertarik melakukan kajian lebih mendalam yang melatar belakanginya, akun Instagram ini layak dijadikan penelitian, ditinjau dari proporsi respon dari followersnya 98% positif dan 2% nya tidak. Dilihat dari isi kontennya, postingannya berupa motivasi, segi nilai keislaman yaitu akhlak, akidah dan syariah. Tujuan penelitian ini untuk mengetahui pesan yang terkandung dalam akun Instagram @twitt.sunnah yaitu akidah, syari’ah dan akhlak. Peneliti menggunakan metode analisis deskriptif kualitatif dengan teori semiotika Roland Barthes, kemudian hasil analisa dikaitkan dengan dalil-dalil Al-Quran dan Hadits. Metode penelitian ini menghasilkan temuan data deskriptif berupa kata-kata, bukan angka. Secara keseluruhan hasil analisis dapat disimpulkan bahwa pesan dakwah yang ditemukan pada akun instagram @twitt.sunnah dapat digolongkan, yakni: 5 pesan aqidah, 9 pesan akhlak, 8 pesan syari'ah.